What can health care professionals in the United Kingdom learn from Malawi? - Neville Ron; Neville Jemma (BMC, 2009)
Abstract Debate on how resource-rich countries and their health care professionals should help the plight of sub-Saharan Africa appears locked in a mind-set dominated by gloomy statistics and one-way monetary aid. Having established a project to link primary care clinics based on two-way sharing of education rather than one-way aid, our United Kingdom colleagues often ask us: "But what can we learn from Malawi?" A recent fact-finding visit to Malawi helped us clarify some aspects of health care that may be of relevance to health care professionals in the developed world, including the United Kingdom. This commentary article is focused on encouraging debate and discussion as to how we might wish to re-think our relationship with colleagues in other health care environments and consider how we can work together on a theme of two-way shared learning rather than one-way aid.